A Survey on Middle School Students Psychological Readiness Back to School During Pandemic - Ardila, Syifa; Nurfajrin, Deva; Nurmala, Siti (Counseling AS SYAMIL: Jurnal Ilmiah Bimbingan Konseling Islam, 2021)
Abstract: The purpose of this study was to determine high school students psychological readiness to begin limited face-to-face learning. The descriptive quantitative method is used in this study. Questionnaires distributed online were used to collect data. There were 25 people who took part in this study. Students in junior high and high school participated in the study. The findings of this study indicate that students are ready for face-to-face learning, though some students are concerned about the spread of the Covid-19 virus. The students also claimed that they could adjust to their new school environment.